2006
DOI: 10.1598/rrq.41.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A primary‐grade teacher's guidance toward small‐group dialogue

Abstract: S The purpose of this study was to describe how one primary teacher of poor and working class rural students promoted small‐group dialogue about books and literary concepts. Specifically, we focused on how she guided the students from the beginning of a lesson in ways that later led to dialogue during a videotaped four‐day lesson sequence. We analyzed interactions of teacher‐student talk during the sequence that involved reading, talking about, and responding to mysteries. Coding involved labeling “indicators”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…Research demonstrates that the conversations surrounding a text have a significant impact on reading instruction because they can influence and support children's development of comprehension strategies as well as their self-perceptions as readers (Almasi, O'Flahavan, & Arya, 2001;Aukerman, Belfatti, & Santori, 2008;Boyd & Rubin, 2006;McIntyre, Kyle, & Moore, 2006;Parker & Hurry, 2007). Most of the studies regarding literature-based discussions have occurred with upper elementary and secondary students; yet studies have demonstrated that young students benefit in many ways when they have the opportunities to participate in classroom discussions that encourage their contributions.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research demonstrates that the conversations surrounding a text have a significant impact on reading instruction because they can influence and support children's development of comprehension strategies as well as their self-perceptions as readers (Almasi, O'Flahavan, & Arya, 2001;Aukerman, Belfatti, & Santori, 2008;Boyd & Rubin, 2006;McIntyre, Kyle, & Moore, 2006;Parker & Hurry, 2007). Most of the studies regarding literature-based discussions have occurred with upper elementary and secondary students; yet studies have demonstrated that young students benefit in many ways when they have the opportunities to participate in classroom discussions that encourage their contributions.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Most of the studies regarding literature-based discussions have occurred with upper elementary and secondary students; yet studies have demonstrated that young students benefit in many ways when they have the opportunities to participate in classroom discussions that encourage their contributions. McIntyre et al (2006) found that young students demonstrated engaged and complex reading responses as a result of participating in conversations that had a balance of teacher support and student direction. They noted how a second-grade teacher used ''fronting strategies,'' which offered direct modeling based on literacy practices she wanted her students to develop or background knowledge needed to understand the text.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Such 'rules of behavior' delivered in the context of teacher-led discussions were insufficient to bring students like Andrea closer in their instinctive project of getting to 'know' Harry. McIntyre, Kyle, and Moore (2006) suggest that teacher-fronted discussions may permit eventual room for dialogic understandings. In that study, the authors illustrate that in the context of a larger classroom discourse on equity and community, the teacher's deliberate use of teacher-fronted conversation followed by dialogic moves led ultimately to evidence of increased conceptual understanding in student work.…”
Section: Scaffolding Peer Understandings Of Disabilitymentioning
confidence: 99%
“…Second, she served as primary facilitator of classroom interactions. Gail facilitated a democratic classroom (Greene, 1988;McIntyre, Kyle, & Moore, 2006), with students working collaboratively to achieve shared goals. Finally, through her position as teacher of reading, Gail modeled reading comprehension and explicitly taught vocabulary, text features, and other concepts related to reading.…”
Section: Social Positionsmentioning
confidence: 99%